Developing an Instrument to Evaluate Psychosocial and Environmental Determinants of Parental Monitoring of Sugar-Sweetened Beverages - Branscum, Paul; Housley, Alexandra (International Journal of Child Health and Nutrition, 2015)
Sugar-sweetened beverage (SSB) consumption among children and adolescents is a public health concern, as up to 88% consume them on a daily basis. While much research has been done regarding what types of foods parents feed their children and how that is linked to various health outcomes, research determining how parents monitor there children’s SSB consumption has not been well studied. Identifying important environmental and psychosocial determinants of parental-monitoring behaviors is a greatly needed area for investigation. The purpose of this study was to develop and validate a theory-based instrument related to this parenting practice. Initially, a 41-item instrument was developed and face and content validity were established using a panel of 6 experts. Next, the survey was administered to 270 parents (29 parents completed the survey twice). Psychometric properties tested of the instrument included construct validity, using the maximum likelihood extraction method of factor analysis, internal consistency reliability, using Cronbach’s alpha, and test-retest reliability using Pearson-product moment correlations between instrument results taken at two separate occasions. Initial results suggested some scales required re-specification, which included removing weak and/or non-related items. Results from this study can be used to assist future health professionals and researchers for measuring theory-based determinants of parental practices related to monitoring SSB consumption. This process can also be replicated to construct instruments measuring other critical obesogenic behaviors, such as monitoring fruit and vegetable consumption, or physical activity.